Mozambique : Financial Sector Assessment - World Bank (Washington, DC, 2013)
Mozambique's overall macroeconomic performance in recent years has been impressive. Macroeconomic stability, a sustained structural reform effort, substantial foreign aid flows and, until recently, a benign international environment has generated an average annual real gross domestic product (GDP) growth rate of 7½ percent for most of the past decade. While inflation has been relatively high (around 10 percent annually) and volatile in recent years, reflecting the predominance of food (52 percent) and energy (23 percent) in the consumer basket, underlying inflationary pressures appear to be contained. As a result, the banking sector's soundness, in particular asset quality, improved substantially. Between end-2003 and 2008, non-performing loans (NPLs) for the system as a whole declined dramatically (from 14.4 to 2.9 percent), largely reflecting the restructuring of problem banks and assets and a supportive macroeconomic environment. This Financial Sector Assessment (FSA) focuses on the key developmental challenges still facing the Mozambican financial sector. Section two provides an assessment of the structure and performance of the banking sector and the main impediments to financial deepening and outreach. Section three presents the state of development and key challenges in the pension and insurance sectors, respectively. Section four assesses the payments system infrastructure.